Implementação do PPVIDA no município de João Pessoa: eficiência e eficácia da construção da política pública sob a ótica do ativismo judicial - Silva Júnior, Aderaldo Cavalcanti da (2019)
The Program of Protection of Life of the City Hall of João Pessoa - PPVIDA is a municipal public policy created from the action of the judiciary provoked by the prosecutor through a public civil action. It is a public policy aimed at protecting children and adolescents threatened with death in the municipality, one of the only municipal initiatives of its kind in Brazil. Against this background, this research is dedicated to investigating to what extent a public policy created from an act of judicial activism can be effective and efficient. From these two guiding concepts - effectiveness and efficiency - a quantitative and descriptive analysis of PPVIDA is promoted, analyzing various data that allow it to become a case study on public policies and judicial activism. The research analyzes public policy models, the institutional design of the Protection Network, as well as the role of program entry doors and analysis of threatened children and adolescents from various perspectives. The data substantiated by PPVIDA were systematized from primary documentary sources and refer to the period from 2012 to 2019. As this is a municipal public policy in the area of public security and social assistance, the guiding hypothesis is that the PPVIDA is an efficient and effective operational strategy that outlines a new way of delivering public policies to protect the lives of children and adolescents threatened with death. The results show that the protection of children and adolescents occurs both in the context of the complexity of urban violence resulting, above all, from drug trafficking, but also from domestic violence itself, revenge for infractions committed, among other situations. The proposed reflection is on the efficiency and effectiveness of PPVIDA in the light of judicial activism.